Halley - Murtagh, Terence ([S.l.] : York Films/ Cal Video, 1985)
'The programme recounts the history of Halley's Comet from earliest times.It examines the origin and nature of comets in general and provides an explanation for the phenomenon' Catalogue
Animation, Paul Ashdown, et. al.;original music, Ernie Wood
Keywords: Halley's comet